2021
DOI: 10.1038/s41391-021-00463-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival by race in men with chemotherapy-naive enzalutamide- or abiraterone-treated metastatic castration-resistant prostate cancer

Abstract: Background Black men are more likely to be diagnosed with aggressive prostate cancer (PC) and die from PC than white men. However, black men with metastatic castration-resistant PC (mCRPC) had longer overall survival (OS) than white men when treated with certain agents in clinical trials. We analyzed claims data from the Veterans Health Administration (VHA) database to evaluate OS in black and white men treated with enzalutamide or abiraterone (novel hormonal therapy [NHT]) for chemotherapy-naïve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…A few studies have shown that Black men tend to have a more significant PSA response (≥50% PSA level decline) than White men when treated with NHTs [20,21]. In this study, Black men with chemotherapy-naïve PC had improved clinical survival outcomes (cPFS) compared with White men, a result that is consistent with previous evidence showing that Black men with mCRPC have a reduced risk of progression and better OS when treated with NHTs and other life-prolonging therapies [20,26,27]. These prior studies on NHTs combined data from enzalutamide plus abiraterone or analyzed abiraterone alone, unlike the current study, which focused only on enzalutamide and addressed the limited amount of real-world PSA response literature for enzalutamide treatment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A few studies have shown that Black men tend to have a more significant PSA response (≥50% PSA level decline) than White men when treated with NHTs [20,21]. In this study, Black men with chemotherapy-naïve PC had improved clinical survival outcomes (cPFS) compared with White men, a result that is consistent with previous evidence showing that Black men with mCRPC have a reduced risk of progression and better OS when treated with NHTs and other life-prolonging therapies [20,26,27]. These prior studies on NHTs combined data from enzalutamide plus abiraterone or analyzed abiraterone alone, unlike the current study, which focused only on enzalutamide and addressed the limited amount of real-world PSA response literature for enzalutamide treatment.…”
Section: Discussionsupporting
confidence: 88%
“…A growing body of evidence suggests the clinical benefit of enzalutamide for the treatment of advanced PC in Black and White men [20,21,26]. A few studies have shown that Black men tend to have a more significant PSA response (≥50% PSA level decline) than White men when treated with NHTs [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an increasing number of studies have valued race in cancer treatment. A study evaluated survival by race in men with chemotherapy-naive enzalutamide- or abiraterone-treated mCRPC and suggested that black men may have better outcomes than white men [ 37 ]. In line with this, another study reported that black men had a statistically significant increase in OS compared to white men [ 38 ].…”
Section: Discussionmentioning
confidence: 99%